FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Emilia Gustini (Jurnal Ilmiah Ekonomi Global Masa Kini)
This research purposes to know factors intrinsic and extrinsic the impact intention accounting information system. The   research used data that obtained from individual perception of accounting information system user in manufacture company the have losted at Bursa Efek Indonesia in Jakarta and branch officer in Palembang. Data to sent by email and Post officer Indonesia. Night hundred  twelve questionnaires have sent to company, seventy questionnaires were return. The data analyzed by using multiple regression by SPSS 11.5 software. Research result show that gender and facilitating conditions user are significant positive influence to intention accounting information system usage, while experiment, voluntariness user, education and training no influence intention accounting information system usage.